PEMANFAATAN APLIKASI KVISOFT FLIPBOOK MAKER DALAM PEMBELAJARAN DI ERA REVOLUSI INDUSTRI 4.0 - Lubis, Nurhidayah (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
Innovation and data hold a significant job as the principal wellspring of learning exercises in the period of modern upset 4.0 which changes generally manual frameworks into advanced frameworks. The reason for computerized learning is to furnish understudies with another learning circumstance and learning environment on the grounds that customary learning techniques are presently not appropriate for the ongoing understudy learning circumstance. Utilizing a variety of learning applications, which make it easier for learning activities to be more efficient and effective while also expanding knowledge, is one way to make use of technology. The goal of this study was to find out how the Kvisoft Flipbook Maker app is used in education during the Industrial Revolution 4.0 era. A relevant literature review was used in this scientific study, which contributes to the research's discussion. Learning using the Kvisoft Flipbook Creator application which is one of the product that can change over PDF records into intuitive advanced books as an elective answer for help understudy learning in the time of the Modern Upset 4.0. As a result, making digital books out of learning materials is a smart way to create a more engaging, interactive, and communicative learning environment and help students comprehend what the teacher is teaching.